Objective Characterization on the Dynamic Friction Coefficient of Disc Brake. Issue 6 (1st November 2016) - Yin, Yan; Bao, Jiusheng; Xiao, Xingming; Liu, Jinge; Lu, Yuhao
ABSTRACT: As the most significant parameter for evaluating the friction state of disc brakes, the friction coefficient was characterized solely by its average and stability coefficient, which cannot accurately represent its dynamic variation characteristics during braking. In this article, a new characterization parameter set consisting of an overall and a partial characteristic parameters subset was established to characterize the dynamic variation in friction coefficient of disc brakes. Moreover, the influence of braking conditions on these new parameter sets was studied by tribological experiments. Several simulated braking experiments were carried out and the dynamic variation rules were observed. Secondly, a new characterization parameter set including eight parameters (mean value, stability coefficient, energy coefficient, end point of rapid rising, starting and end points of the up-tail, trend coefficient, and catastrophe coefficient) was established. Finally, the influence of initial braking velocity and braking pressure on these parameters and its mechanism was analyzed by braking experiments. It is concluded that the parameter set established in this article can be used to characterize the dynamic variation rules of the friction coefficient of disc brakes more objectively and comprehensively.